Open Banking and Regulatory Challenges in Indonesia - Muhamad Agung Dharmajaya (Jurnal Restorasi : Hukum dan Politik, 2023)
The acceleration of digitalization is driving the Indonesian financial sector to transform from a conventional operational model to an open banking ecosystem. This study aims to analyze the development of open banking implementation in Indonesia and identify key regulatory challenges faced in mitigating legal and cybersecurity risks. The research method used is a normative juridical approach with a qualitative-descriptive approach through secondary data analysis in the form of Bank Indonesia regulations, the Financial Services Authority (OJK), and related literature. The results in the first sub-chapter indicate that the implementation of open banking, guided by the National Standard for Open API Payments (SNAP), based on the 2025 Indonesian Payment System Blueprint (BSPI), has successfully increased financial inclusion and the efficiency of system integration between financial actors. However, the analysis in the second sub-chapter reveals significant regulatory challenges, including an expanded cyberattack surface due to imbalances in IT protection capacity, uncertainty about legal liability in the event of system failures, fragmented cross-sectoral oversight, and difficulties in synchronizing with the Personal Data Protection Law (PDP Law). This research concludes that advances in SNAP's technical infrastructure have not been matched by an adaptive legal framework, creating legal gaps that risk consumer harm. This research recommends that Bank Indonesia and the Financial Services Authority (OJK) formulate joint regulations, shift to a principles-based approach, and strengthen the capacity of supervisory technology to create a safe and sustainable digital financial ecosystem.